Sentidos e significados de egressos da licenciatura em matemática à sua formação inicial - Voigt, Jane Mery Richter (2012)
Especially in the last decade, there has been great change in the nature of the curriculum components in the undergraduate degree courses (licensures). The syllabus has included more intensely pedagogical disciplines and there has been a greater integration of these disciplines with the specific disciplines of the course. Having in mind these aspects, the aim of this research is to investigate the senses and meanings that a group of Mathematics teaching course graduates attributes to the initial education, considering their teaching practice that has been developed at the time of the investigation as constituent mediations of such meanings. As the theoretical and methodological assumption, the dialectical and historical materialism is adopted. The participants of the research were graduates in Mathematics teaching course from a university of Santa Catarina, who finished the course in 2007, 2008 and 2009. The instrument used to collect the data was a questionnaire with open and closed questions and an interview. The analysis of the questionnaire allowed the selection of four individuals to be interviewed, and the choice of some topics to be further developed in the second stage of the data collection. The analysis of the data collected through the interview was conducted in accordance with the proposal called Core of Meaning by Aguiar and Ozella (2006). The results indicate important aspects related to the initial education: the institutional conditions during the indicial education as significant for the graduates performance and education; the pedagogic aspects as fundamental to the teacher education; the example of the professors practice and the exchange of experiences with the classmates. The meanings about the practice of the graduates reveal the concern with their own students learning, for example they consider the students previous knowledge establishing a dialogue with the new knowledge. However the course also reinforces the dichotomy between theory and practice, particularly regarding to the pre-service teacher training. It is understood that the initial education courses have a very important role in all aspects of professional development, engaging with the context and culture in which it develops